THE CORRELATION BETWEEN MENOPAUSAL SYMPTOMS AND SEXUAL FUNCTION IN MENOPAUSAL WOMEN - Pangruating Diyu, Ida Ayu Ningrat; Tri Agustini, Ni Komang (Universitas Islam Negeri Alauddin Makassar, 2021)
Sexual function is important issue in women health. Sexual function could be affected by several factors in menopausal women. This study aimed to investigate relationship between menopausal symptoms and sexual function. Cross sectional study design was used in this study. This study conducted among 372 menopause women aged 45-65 years. The Stages of Reproductive Ageing Workshop (STRAW +10) was used to identified participant who were in pre, peri and post-menopausal stages. The instrument used for data collection were the Female Sexual Function Index (FSFI), the Menopause Rating Scale (MRS) and demographic questionnaire. Chi-square and Spearman correlation was used to analyze correlation between variables. The result showed the was 88.7 % of the participants had female sexual dysfunction (FSFI≤26.55). A significant correlation was observed between menopausal symptoms (somatic, psychology and urogenital) and sexual dysfunction (P<0.001). the results of spearman correlation analysis showed significant negative correlation between urogenital symptoms and desire (r=-0.12,p=0.020), all subscale of menopausal symptoms and lubrication (somatic [r=-0.30,p<0.001], psychology [r=-0.29,p<0.001] dan urogenital [r=-0.27,p<0.001]), urogenital symptoms and orgasms (r=-0.17,p=0.024),urogenital and somatic with satisfaction (somatic [r=-0.11,p<0.027], urogenital [r=-0.11,p<0.034] and all of menopausal symptoms subscale with pain (somatic [r=-0.15,p=0.002], psychology [r=-0.21,p<0.001] dan urogenital [r=-0.16,p=0.002]). We conclude the importance of assessing menopausal symptoms as part of sexuality in menopausal women and need to be considered in the design health initiatives at menopause’s sexual function Keywords: Menopause, sexual dysfunction, Female Sexual Function Index (FSFI), menopausal symptoms, Menopause Rating Scale (MRS)